Fabrication of Si3N4 nanowire membranes: free standing disordered nanopapers and aligned nanowire assemblies. (16th August 2016) - Liu, Haitao; Fang, Minghao; Huang, Zhaohui; Huang, Juntong; Liu, Yan-gai; Wu, Xiaowen
Abstract: Herein, ultralong silicon nitride nanowires were synthesized via a chemical vapor deposition method by using the low-cost quartz and silicon powder as raw materials. Simple processes were used for the fabrication of disordered and ordered nanowire membranes of pure silicon nitride nanowires. The nanowires in the disordered nanopapers are intertwined with each other to form a paper-like structure which exhibit excellent flame retardancy and mechanical properties. Fourier-transform infrared spectroscopy and thermal gravity analysis were employed to characterize the refractory performance of the disordered nanopapers. Highly ordered nanowire membranes were also assembled through a three-phase assembly approach which make the Si3 N4 nanowires have potential use in textured ceramics and semiconductor field. Moreover, the surface nanowires can also be modified to be hydrophobic; this characteristic make the as-prepared nanowires have the potential to be assembled by the more effective Langmuir–Blodgett method and also make the disordered nanopapers possess a super-hydrophobic surface.